The Implementation of Batik Tanjung Bumi Philosophy Value in Cross Culture Understanding Classroom - Tera Athena; Nur Aini S; Mety Liesdiani (English Teaching Journal : A Journal of English Literature, Language and Education, 2022)
Batik is part of local wisdom that exists in the Madurese community and is an ancestral heritage that needs to be preserved. This preservation can be applied by linking the Batik philosophy to Cross Culture Understanding learning which emphasizes the background of certain motifs that describe the life of the Madurese community. Through the qualitative method, the author tries to explore the reflection of the philosophy of the Tanjung Bumi Batik Motif. The motifs and colors of Tanjung Bumi Batik tell some aspects of the life of the Madurese community and the symbols of the habits of the Madurese people in general. Linking the Philosophical Values of the Tanjung Bumi Batik Motif will add real insight into the life of the Madurese community. This can also motivate teachers to implement learning in lectures.